PEMANFAATAN FOTOKATALIS TiO2 UNTUK MEREDUKSI ION TIMBAL - Kapti Riyani; Tien Setyaningtyas (Universitas Jenderal Soedirman, 2009)
TiO2 photocatalyst can be used to reduce heavy metal ions into common metal ion or metal ion with lower coordination number. This research aimed to (1) study the influence of pH on the photoreduction activity of Pb2+ion by TiO2, (2) study the influence of hole scavenger on the photoreduction activity of Pb2+ ion by TiO2, (3) study the influence of light source on the photoreduction activity of Pb2+ ion by TiO2. The method used on this research is laboratory experiment consist of the making of TiO2 thin film, standard Pb2+ photoreduction with the variation of pH, standard Pb2+ photoreduction with the variation of light source. The results of Pb2+ photoreduction are analyzed by Atomic Absorption Spectroscopy. The result of the research showed that the activity of TiO2 to reduce Pb2+ can be optimum at pH 6, oxalic acid as hole scavenger and UV lamp use. The sunlight can also be used as the light source to reduce Pb2+ by TiO2 photocatalyst.